2016
DOI: 10.1080/10400419.2016.1195653
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Creativity and Real-Life Involvement in Different Types of Creative Leisure Activities

Abstract: The role of emotional creativity in practicing creative leisure activities and in the preference of college majors remains unknown. The present study aims to explore how emotional creativity measured by the Emotional Creativity Inventory (ECI; Averill, 1999) is interrelated with the real-life involvement in different types of specific creative leisure activities and with four categories of college majors. Data were collected from 251 university students, university graduates and young adults (156 women and 95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
1
26
0
2
Order By: Relevance
“…Therefore, it is not surprising that higher EC has been found to be related to the increased involvement of participants in creative leisure-time activities, e.g. creative writing, painting, composing music, dance improvisation, theatrical improvisation and do-ityourself activities (Trnka, Zahradnik, & Kuška, 2016).…”
mentioning
confidence: 99%
“…Therefore, it is not surprising that higher EC has been found to be related to the increased involvement of participants in creative leisure-time activities, e.g. creative writing, painting, composing music, dance improvisation, theatrical improvisation and do-ityourself activities (Trnka, Zahradnik, & Kuška, 2016).…”
mentioning
confidence: 99%
“…Such influences are not limited to economic knowledge and experience. The subject's emotional and evaluative attitude to the problem also influences creativity, which has already been the subject of special research (Ivcevic et al, 2007;Trnka et al, 2016). "Aesthetic intelligentsia", by Pauline Brown.…”
Section: Resultsmentioning
confidence: 99%
“…From the study, it was observed that the participants were able to reflect on their own creative abilities and their actions in different contexts. Expressions referred to creativity as potential of all people that can be developed in different contexts, a definition with which most current researchers of creative processes seem to agree (Glaveanu, 2018;Richards, 2010;Trnka, Zahradnik & Kuška, 2016).…”
Section: Creative Self-beliefsmentioning
confidence: 99%
“…Creativity is a potentiality all people have that can develop in different domains and contexts. The arts, sciences, technology, social relations, emotions and daily life are fields where it is possible to develop original ideas and products (Glaveanu, 2018;Richards, 2010;Trnka, Zahradnik & Kuška, 2016). According to UNESCO, creativity refers to the ability of people to solve problems and transform reality.…”
Section: Introductionmentioning
confidence: 99%